Physiotherapy in tennis injuries - Zverbíková, J.; Šimurdová, N.; Malay, M. (Zdravotnícke listy, 2019)
Background: Tennis belongs to the sports with unilateral loading that affects body posture, muscle imbalance, trigger points, overload of the locomotive apparatus, causes the breakdown of functional disorders that results in tennis injuries. Objective: The aim of the study was the use and monitoring the effectiveness of individual physiotherapy methodologies with the possibility to use it in tennis injuries. Sample: The study presents two case studies. A man diagnosed with epicondylitis lateralis humeri l.dx. was 19-year old and a 23-year old man was diagnosed with impingement syndrome of the shoulder joint on the right. Both men were active tennis players with a game load of 6-10 hours per week. Methods: The rehabilitation took place individually in the private rehabilitation center in Žilina and in the patients' home environment. In the survey we used a qualitative method of a case report. Results: The applied rehabilitation methodology has brought the improved condition of a patient with lateral epicondylitis of the elbow and impingement syndrome. The inhibition of soft tissues and muscle tension by kinesiotype, post-isometric relaxation for muscle shortening and the SM system, which contributed